Looking for growth imperatives under capitalism: money, wage labour, and market exchange - Louison Cahen-Fourot (Post-growth Economics Network (PEN), 2022)
First, I update and wrap up the discussion on a monetary growth imperative, namely the argument that debt-money bearing interest triggers real GDP growth. I provide a detailed account of the different versions of the argument and show why none of them hold. In all cases, the argument is shown to be inconsistent in macro-accounting terms or to be at odds with the functioning of the monetary system. The general solution to the monetary growth imperative is that a sufficient share of wealth must be put back in circulation, for example via higher consumption out of wealth or taxation. Moreover, I show that a monetary growth imperative could equally well occur in an economy without debt-money or interest. However, the solution to the monetary growth imperative entails a sustainability paradox: more wealth put back in circulation allows to reach a stable full stationary state but may be environmentally unsustainable. I also highlight convergences between the critique of the monetary growth imperative and the monetary circuit literature. Second, I address the criticism that no net wealth accumulation is unrealistic. It requires to explain why there is accumulation in the first place. Building from post-Keynesian and institutionalist perspectives, I argue that we need to locate the analysis at the level of the definitional social relations of capitalism: market exchange and wage labour. Growth imperatives are emerging properties of these two social relations. I develop a critique of steadystate economics and underline the ontological difference between a zero-growth capitalism and a post-growth economy.
Keywords: E21; E24; E43; B52; P1; 330; growth imperative; capitalism; paradox of profit; ecological macroeconomics; post-growth